Neuromuscular recovery in ACL reconstruction with Bone-Tendon-Patellar-Bone and Semitendinosus-Gracilis autograft - Pasquini, Andrea; Jacopetti, Marco; Pogliacomi, Francesco; Ramazzina, Ileana; Costantino, Cosimo (Acta Biomedica Atenei Parmensis, 2017)
Objective: Several different types of grafts have been used in ACL rupture. The purpose of the study was to compare the recovery of lower limbs muscle strength and proprioception in athletes, who underwent ACL reconstruction with Bone-Patellar-Tendon-Bone (BPTB) versus semitendinosus and gracilis (HS) autografts. Methods: We enrolled 30 male amateur athletes. Each patient was evaluated by isokinetic test, triaxial accelerometer test and balance test with stabilometric platform. Isokinetic test evaluated quadriceps and hamstrings Peak Torque. Accelerometer test evaluated squat jump test (SJT) and stiffness test (ST). The recording on the balance platform was performed with open and closed eyes and evaluated medio-lateral and anterior-posterior pathways. Results: 30 patients were selected (15 in group BPTB and 15 in group HS). In SJT we noticed a statistically significant difference in height of jump in the involved side in favour of Group BPTB (p=0.037) and not significant difference in the other parameters. In the ST, we did not observe significant statistical differences in the parameters of the test. The stabilometric platform data and isokinetic peak torque parameters did not show a significant difference. Discussion: Little high quality researches are available to help determine when patients can safely return to full activity and sport. Included evaluation criteria were a combination of factors regarding knee motion, muscles strength and neuromuscular function. Conclusion: In our study, despite a not full recovery of explosive strength in HS group , the balance and the other parameters after one year are comparable between the two graft. In our findings there isn’t clinical difference between the two grafts. We suggest that the evaluation of explosive strength and proprioception are the priority parameters in neuromuscular recovery after ACL reconstruction.